Energy Consumption, Democracy, and Income Inequality in Africa - Samuel Adams; Isaac K. Ofori; Emmanuel Y. Gbolonyo (ZBW - Leibniz Information Centre for Economics, 2025)
This study employs macro-level data from 33 African countries to examine the impact of energy consumption (disaggregated into renewable and non-renewable sources) on income inequality. It further investigates the moderating role of five distinct democracy typologies – liberal, electoral, deliberative, participatory, and egalitarian – within the energy-inequality nexus. Employing the dynamic GMM estimator, the analysis accounts for the persistence of income inequality and mitigates endogeneity concerns. The findings reveal that energy consumption plays a significant role in reducing income inequality across Africa. The interactive analysis also demonstrates that the income-equalising effect of non-renewable energy is particularly pronounced. Moreover, while all democracy typologies amplify the inequality-reducing effect of non-renewable energy, only participatory and egalitarian democracies enhance the impact of renewable energy. These results underscore the nuanced and asymmetric influence of energy types on income distribution in Africa, with non-renewable energy exhibiting more substantial direct and conditional effects. The study concludes by outlining key policy implications to foster equitable growth.
Keywords: D63; H11; O43; O55; Q01; Q43; 330; Africa; Democracy; Energy consumption; Renewable energy consumption; Non-renewable energy consumption; Income inequality